Stripped of Dignity and Murdered: A case report - Talukdar, R; Ropmay, AD; Patowary , AJ; Slong, D (Journal of Indian Academy of Forensic Medicine, 2024)
India has shown utter disregard and disrespect for women - rape, marital rape, sexual assault, harassment, female infanticide and dowry death are the best examples to cite this. These issues have been on debate for years after years with no definite result. Nearly 31,000 complaints of crimes committed against women were received by the National Commission for Women (NCW) in 2022, the highest since 2014.This is a case of an unidentified woman of about 24 years approx. who was found dead in the Jungles, Shillong. She was referred for post mortem examination to the department of Forensic Medicine in a tertiary hospital in North-East India. Autopsy findings revealed abrasions and bruises on the head and neck region with a ligature mark on the front and right side of neck. Internal organs were congested. Uterus and ovaries showed contusions. Fresh hymenal and perineal tear seen. There was evidence of spermatozoa in vaginal smear on microscopic examination. Assault against women is related with harmful health consequences and is regarded as a major public health problem. It is also a barrier for sustainable development goal of women on gender equality empowerment. The women facing brutality are more likely to view health workers as trustworthy for disclosure of abuse, hence it should be properly structured.
Keywords: Assault against women; Rape; Murder